Transport economics in Peru, 1800-1914 - Contreras Carranza, Carlos (Universidad del Pacífico, 2010)
Account of the misfortune that traders and producers had to endure in the XIX century Peru to transfer their merchandise because of the difficulties in transportation; of how it was somewhat lightened or transformed through the innovation of the railway; but also, of how muleteers, cattle carriers, farmers and vets, who formerly supplied mules, produced the fodder to feed them, and cured their multiple ailments, suffered with this change.